Effects of transcranial direct current stimulation over the posterior parietal cortex on novice X-ray screening performance. (November 2020) - Wagner, Jennifer; Lo Monaco, Silvia; Contò, Federica; Parrott, Danielle; Battelli, Lorella; Rusconi, Elena
Abstract: Existing theories of visual search are generally deduced from lab-based studies involving the identification of a target object among similar distractors. The role of the right parietal cortex in visual search is well-established. However, less is known about real-world visual search tasks, such as X-ray screening, which require targets to be disembedded from their background. Research has shown variations in the cognitive abilities required for these tasks and typical lab-based visual search tasks. Thus, the findings of traditional visual search studies do not always transfer into the applied domain. Although brain imaging studies have offered insights into visual search tasks involving disembedding, highlighting an association between the left parietal cortex and disembedding performance, no causal link has yet been established. To this end, we carried out a pilot study ( n = 34, between-subjects) administering non-invasive brain stimulation over the posterior parietal cortex (PPC) prior to completing a security X-ray screening task. The findings suggested that anodal left PPC tDCS enhanced novice performance in X-ray screening over that of sham stimulation, in line with brain imaging findings. However, the efficacy of tDCS is under question, with a growing number of failed replications. With this in mind, this study aims to re-test our original hypothesis by examining the effects of left-side parietal stimulation on novice X-ray screener performance and comparing them to those of sham stimulation and of stimulation on a control site (right PPC). As such, this within-subjects study comprised three sessions (2 mA left PPC, 2 mA right PPC, low-intensity sham stimulation left PPC), to investigate effects of anodal tDCS on X-ray screening performance. The pre-registered analysis did not detect any significant differences between left PPC tDCS and sham tDCS or left PPC tDCS and right PPC tDCS on novice performance (d′) in X-ray screening. Further exploratory analyses detected no effects of left PPC tDCS on any other indices of performance in the X-ray security screening task (c, RTs and accuracy), or a disembedding control task (RTs and accuracy). The use of alternative stimulation techniques, with replicable behavioural effects on the parietal lobe (or a multi-technique approach), and well-powered studies with a systematic variation of stimulation parameters, could help to choose between two possible interpretations: that neither left nor right PPC are causally related to either tasks or that tDCS was ineffective. Finally, low-intensity sham stimulation (.016 mA), previously shown to outperform other sham conditions in between-subjects designs, was found to be ineffective for blinding participants in a within-subjects design. Our findings raise concerns for the current lack of optimal control conditions and add to the growing literature highlighting the need for replication in the field.